Suppressing ERK Pathway Impairs Glycochenodeoxycholate-Mediated Survival and Drug-Resistance in Hepatocellular Carcinoma Cells - Li, Bingxin; Zhou, Maojun; Wang, Jue; Xu, Hongjuan; Yang, Manyi (Frontiers in Oncology, 2021)
Glycochenodeoxycholate (GCDA), a toxic component in bile salts, is involved in carcinogenesis of gastrointestinal tumours. The objective of this research was to study the function of ERK1/2 in the GCDA mediated survival and drug-resistance in hepatocellular carcinoma cells (HCC). Firstly, extracellular signal-regulated kinase 1/2 (ERK1/2) was detected extensively expressed in liver cancer cells , and silencing ERK1/2 by RNA interference could suppress GCDA-stimulated survival and promote apoptosis. Furthermore, phosphorylation of endogenous ERK1/2 could be potently stimulated by GCDA in combination with enhanced chemoresistance in QGY-7703 hepatocellular carcinoma cells. The GCDA-mediated proliferation and chemoresistance could be impaired by PD98059, which acted as an inhibitor to block the phosphorylation of ERK1/2. Mechanistically, PD98059 was able to potently suppress GCDA-stimulated nuclear aggregation of ERK1/2 and p-ERK1/2, up-regulate pro-survival protein Mcl-1 and down-regulate pro-apoptotic protein Bim. The results of this study indicated that disruption of ERK1/2 by blocking phosphorylation or nuclear translocation may put forward new methods for solving the problem of GCDA-related proliferation and drug-resistance in liver cancer treatment.